Particle size determines the efficiency of calcitic limestone in amending acidic soil - Scott, B.J; Conyers, M.K; Fisher, R; Lill, W. (New South Wales Agriculture, Wagga Wagga (Australia). Agricultural Research Inst.) (Australian journal of agricultural research, 1992)
A field experiment was conducted using 6 particle size segregations of calcitic limestone covering a range of mean diameters from 3 mm to 0.005 mm. These products were applied at rates of 2.5, 5 and 10 t per ha. No minimum particle size for maximum effectiveness was identified. Throughout the range of particle sizes evaluated, progressively finer particles produced larger increases in pH and exchangeable Ca. Wheat yield was related to soil pH. Changes in soil pH and exchangeable Ca between 6 months and 3 years after lime application were small compared to the changes in the first 6 months. Fine lime products should be preferred in practice, subject to cost considerations and handling difficulties.